Estimation of multivariate distributions for recurrent event data - Machado, Luís Meira (2017)
In many longitudinal studies information is collected on the times of different kinds of events. Some of these studies involve repeated events, where a subject or sample unit may experience a well-defined event several times along his history. Such events are called recurrent events. In this work we consider the estimation of the marginal and joint distribution functions of two gap times under univariate random right censoring. We also consider the estimation of the bivariate survival function.